A influência do clima organizacional no bem-estar no trabalho: estudo nas empresas terceirizadas da Universidade Federal do Tocantins - Campus de Araguaína - Souza, Ana Augusta Carneiro de (Universidade Federal do Tocantins, 2020)
Taking into account the dynamism of the work environments that require greater dedication and affectivity in relation to its employees, this study seeks to verify the effect of the organizational climate on the welfare of outsourced employees of the Federal University of Tocantins. Participants are workers who work in different companies and in different functions. As an instrument for data collection, a self-completion questionnaire was used, composed of four scales that measured the variables of the research. It was also proposed to present, interpret relations between variables, as well as test hypotheses referring to the proposed conceptual model, through a transversal research with a quantitative approach, in which the data were analyzed by applying statistical techniques. The results showed that there are positive relations between the factors of organizational climate and well being at work. Finally, this study showed that when employees perceive that the climate is pleasant tend to have a more favorable state for well being at work.